2013
DOI: 10.1007/s10157-013-0920-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of kidney function and urinary protein excretion on pulmonary function in Japanese patients with chronic kidney disease

Abstract: This study suggests that decreased eGFR is associated with decreased %DLCO in proteinuric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Additionally, it is also an independent risk factor of cardiovascular events and mortality [ 8 ]. Although previous studies have identified a relationship between pulmonary function and UACR as well as chronic kidney disease with reduced estimated glomerular filtration rate (eGFR) [ 9 11 ], few studies focus on the T2DM patients with preserved eGFR. As we know, those with T2DM are more likely to have albuminuria and at a higher risk for cardiovascular disease even with preserved eGFR [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is also an independent risk factor of cardiovascular events and mortality [ 8 ]. Although previous studies have identified a relationship between pulmonary function and UACR as well as chronic kidney disease with reduced estimated glomerular filtration rate (eGFR) [ 9 11 ], few studies focus on the T2DM patients with preserved eGFR. As we know, those with T2DM are more likely to have albuminuria and at a higher risk for cardiovascular disease even with preserved eGFR [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A small Japanese study also reported that reduced GFR is associated with reduced pulmonary diffusing capacity 17 . In another retrospective longitudinal analysis, an increased risk of chronic kidney disease was associated with decreased airflow as measured by the FEV1/FVC ratio 18 .…”
Section: Discussionmentioning
confidence: 98%
“…Yu et al [ 16 ] found that in a cohort comprising 1454 Australian and 5824 Chinese individuals, an increased risk of reduced renal function was related to obstructive lung function, and that FEV1 and FVC < 3.05 L increased the risk of impaired renal function. A small Japanese study also reported that reduced GFR is associated with reduced pulmonary diffusing capacity [ 17 ]. In another retrospective longitudinal analysis, an increased risk of chronic kidney disease was associated with decreased airflow as measured by the FEV1/FVC ratio [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The National Health and Nutrition Examination Survey 2007–2012 investigated 7610 participants aged 40–79 years and revealed that impaired lung function is common in those with and without chronic kidney disease, and eGFR <60 ml/min/1.73 m2 was associated with higher odds of obstructive lung function [3]. In another small Japanese sample, it was also found that decreased eGFR is associated with decreased pulmonary function markers of pulmonary diffusion capacity [21]. In another cohort study incorporating vascular surgery patients, chronic obstructive pulmonary disease (COPD) was found to be associated with restricted renal function and chronic kidney disease [22].…”
Section: Discussionmentioning
confidence: 99%